COMPETITIVE PRIORITIES IN THE URBAN MOBILITY SECTOR - Oshiro, Estela Tieko; Guimarães, Márcia Regina Neves; Lara, Felipe Ferreira de (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose – The research aims to identify the competitive priorities adopted by a company that operates in the urban mobility services sector and analyzes practices and strategies that reinforce the priorities adopted. Design/methodology/approach – Exploratory case study from a qualitative approach, through semi-structured interviews with four actors relevant to the development of the research problem. Findings – It was possible to observe that the technologies for mobility allows the implementation of innovation based on the perception of the customer's desire, which, in the case of this research, had quality as the central element. A central point identified was the fact that the company under study used innovation when customizing products to maintain competitive levels of quality and differentiation through service innovations. On the other hand, there is a restriction with a greater impact, which is the fact of the difficulty in controlling the levels of services performed by drivers. Originality/value – The research contributes to a better understanding of the customer's needs in the urban mobility services sector, and in order to guarantee higher customer satisfaction and improve the level of quality in the supply of services, resulting in performance and competitive advantage for companies in the sector. Keywords - Competitive priorities; quality; services; innovation.